2013
DOI: 10.1080/09540121.2013.772284
|View full text |Cite
|
Sign up to set email alerts
|

Access to antiretroviral therapy during excess black-water flooding in central Thailand

Abstract: Excess black-water flooding in central Thailand resulted in closure of several healthcare facilities in the Fall of 2011. Persons living with human immunodeficiency virus (HIV) infection were presumably at risk for interruption of antiretroviral therapy (ART), with consequent treatment failure. We conducted a retrospective cohort study of ART use among patients in care at a Thai HIV clinic that closed due to excess flood water. Among 217 patients on ART who had clinic appointments within the one-month interval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 11 publications
0
13
0
Order By: Relevance
“…Five studies reported outcomes in a setting of post-election violence (Unge et al 2010;Pyne-Mercier et al 2011;Bamrah et al 2013;Doumbouya et al 2012;Yoder et al 2012); these studies were undertaken mainly in sub Saharan African, where both HIV and conflicts are most prevalent (Mills et al 2009), including Kenya, Northern Uganda and the Ivory Coast. Three studies reported outcomes from natural disaster settings (Bhakeecheep et al 2012 Walldorf et al 2012;Khawcharoenporn et al 2013). Finally, two studies only reported results for children (Kiboneka et al 2008;Yoder et al 2012).…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
See 3 more Smart Citations
“…Five studies reported outcomes in a setting of post-election violence (Unge et al 2010;Pyne-Mercier et al 2011;Bamrah et al 2013;Doumbouya et al 2012;Yoder et al 2012); these studies were undertaken mainly in sub Saharan African, where both HIV and conflicts are most prevalent (Mills et al 2009), including Kenya, Northern Uganda and the Ivory Coast. Three studies reported outcomes from natural disaster settings (Bhakeecheep et al 2012 Walldorf et al 2012;Khawcharoenporn et al 2013). Finally, two studies only reported results for children (Kiboneka et al 2008;Yoder et al 2012).…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…Nine of the studies did not statistically adjust for confounders and seven studies did not follow up patients for more than six months. Two studies were given a 'higher rating' of overall strength of study quality (Kiboneka et al 2009;Yoder et al 2012), five studies were given a 'medium' rating, (Garang, Odoi, and Kalyango 2009;O'Brien et al 2010;Autino et al 2012;Walldorf et al 2012;Khawcharoenporn et al 2013) and seven studies a 'lower' rating (Kiboneka et al 2008…”
Section: Assessment Of Study Qualitymentioning
confidence: 99%
See 2 more Smart Citations
“…10 The resulting economic and livelihood-related challenges could also have led to adverse consequences related to HIV care access and engagement. 11 , 12 Within the more disadvantaged populations and residents living in these impacted areas, these consequences were experienced in an even greater magnitude. 7 For example, unemployment, food insecurity, financial insecurity, lack of transportation, and inability to afford preventive measures such as physical distancing and protective equipment during this period could have further reduced patient motivation to continue engaging in HIV care.…”
Section: Introductionmentioning
confidence: 99%